TEACHERS’ AND PARENTS’ PERCEPTION ON ENGLISH LANGUAGE POLICY IN ELEMENTARY SCHOOL - Fitri Permata Rahim; Yustika Nur Fajriah (Institut Pendidikan Indonesia Garut, 2021)
Due to the latest alteration of English status in elementary schools in Indonesia; that is, as extracurricular subject, this research aims to find out teachers’ perceptions on the recent English language policy in the primary school level and parents’ perceptions on the deletion of English subject in elementary school. To fulfill this aim, semi-structured interview was used as the instrument in collecting the data. The data were then analyzed inductively through the phases; recording, transcribing, categorizing, and interpreting. As the results, English teachers and parents had the same perceptions on the deletion of English in elementary school stage. Specifically, they disagreed with the abolished of English in Elementary School, almost the participants, not only teachers but also parents, expected English to be included in the curriculum so that the position of English is a local content in elementary school learning, and if possible English is aligned with other subjects. Therefore, the goverment is expected to reconsider this policy about the English status in Elementary school stage.